Economic policy uncertainty on stock market risk contagion: a network-based approach - Shao, Hualu; Wang, Di; Zhou, Baicheng (Frontiers in Physics, 2024)
It is necessary to study the relationship between the dynamical uncertainty and risk contagion in the financial market. In this paper, we use the Economic Policy Uncertainty (EPU) Index, calculate the stock index volatility of the top seven global economies in 2021, then construct a risk spillover network. For the sub-sample analysis, we select three different types of global crises to study the transmission direction and intensity within the risk network across each time period. The results show that firstly, EPU has both direct and indirect effects on risk contagion in cross-country stock markets. It mainly plays an intermediary role. Secondly, in the risk network, the intensity and structure are time-varying, no single country serves as the exclusive issuer or recipient of risk spillovers. Thirdly, the speed and impact of shocks from public health security crises are much greater. In light of the findings above, investors and policymakers in different countries are expected to strengthen cooperation in financial risk prevention and enhance risk early warning. And we provide new evidence to emphasize attention to shocks caused by public health events, aiming to prevent the recurrence of large cross-border financial risks.